Forecasting the Foreign Exchange Reserve of Lao PDR by ARIMA Model - HER, Pheng; PHONPRASITH, Bounthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
Foreign Exchange Reserve (FER) consists of foreign currency, deposits denominated in foreign currency, Monetary Gold, Special Drawing Rights (SDRs) and reserve position in the International Monetary Fund (IMF). It is one of the important macroeconomic to provide confidence, keep markets steady, etc. Autoregressive Integrated Moving Average (ARIMA) model is one of the mostly used approaches to time series forecasting was introduced by Box and Jenkins. Lao PDR is one of the least developed countries which have witnessed rapid economic growth. Since 2000, the foreign exchange reserve of Laos has rapidly increased, but the foreign currency exchange rates and inflation were increased too. Therefore, this paper aims to forecast the monthly foreign exchange reserve of Lao PDR from January 2000 to December 2020 by using ARIMA model. The estimation found that ARIMA (3,1,3) model is an appropriate model for predicting the foreign exchange reserve. The more effectiveness for predicting before 2010, after that the estimated error will be wider and high fluctuation. However, the forecasting value nearly the actual value was on March 2020, differences only 0.22.